2019
DOI: 10.18203/2319-2003.ijbcp20195778
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study in medicine intensive care unit in tertiary care hospital

Abstract: Background: The medical intensive care unit (MICU) is a setting were patients who are critically ill are admitted and thus usually receive a large number of drugs of different pharmacological classes due to life threatening illnesses which may be fatal. The various drugs used in MICU and there clinical outcome was investigated in this study.Methods: Patients admitted between January 2017 to June 2018 in Medicine ICU of GMC Aurangabad were included in this study.Results: Total of 351 prescriptions was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This showed that the trend of prescribing by trade names is not changed over the years. 1,2,4,[7][8][9][10][11][12] The number of injectable drugs prescribed depends on general condition of the patient which would vary in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the trend of prescribing by trade names is not changed over the years. 1,2,4,[7][8][9][10][11][12] The number of injectable drugs prescribed depends on general condition of the patient which would vary in different studies.…”
Section: Discussionmentioning
confidence: 99%